Mechanical Properties and Abrasive Wear of Different Weight Percentage of TiC Filled Basalt Fabric Reinforced Epoxy Composites - Anand Chelliah (Materials Research)
Fiber reinforced polymers are very rarely applied as wear-resistant materials because of the lack of good mechanical strength, which adversely affects the properties of the composites. To improve the mechanical and abrasive wear resistant of the composites, fillers are incorporated into the polymers. Hence in this work composites are produced by adding functional inorganic fillers such as Titanium Carbide (TiC) and basalt fabric as reinforcement. The composites have been fabricated by using vacuum assisted resin transfer moulding (VARTM). Abrasive tests were conducted using pin-on-disc instrument by varying abrasive distances at different loads of 5, 10 and 15N.After the incorporation of TiC filler in basalt fabric reinforced epoxy composite a significant reduction in weight loss were observed. Composites containing 2wt% TiC exhibit the lowest weight loss among other 4 wt % and 6 wt % TiC filled epoxy composites. The surface topography the composites were analyzed by using scanning electron micrographs (SEM).